Axial filament involvement in the motility of Leptospira interrogans. - Bromley, D B (1979)
Motility mutants of Leptospira interrogans serovar illini were isolated and analyzed by dark-field and electron microscopy. Mutants were obtained by screening for small colonies after nitrosoguanidine treatment. One class of mutants did not have hook- or spiral-shaped ends. In addition, the axial filaments from these mutants were not coiled. An analysis of revertants of two of the mutants in this class indicated that the mutations were pleiotropic with respect to motility, hook- and spiral-shaped ends, and axial filament coiling. We conclude that the axial filaments and the hook- and spiral-shaped ends are involved in L. interrogans motility.